2007
DOI: 10.1073/pnas.0700847104
|View full text |Cite
|
Sign up to set email alerts
|

A bile acid-like steroid modulates Caenorhabditis elegans lifespan through nuclear receptor signaling

Abstract: Broad aspects of Caenorhabditis elegans life history, including larval developmental timing, arrest at the dauer diapause, and longevity, are regulated by the nuclear receptor DAF-12. Endogenous DAF-12 ligands are 3-keto bile acid-like steroids, called dafachronic acids, which rescue larval defects of hormone-deficient mutants, such as daf-9/cytochrome P450 and daf-36/Rieske oxygenase, and activate DAF-12. Here we examined the effect of dafachronic acid on pathways controlling lifespan. Dafachronic acid supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
239
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(252 citation statements)
references
References 31 publications
8
239
1
1
Order By: Relevance
“…1). A previous report has shown that DAs are produced in an insulin and TGFb signalling-dependent manner in developing C. elegans under nutrient-favourable conditions 4 . However, we found that DR also induces daf-9 expression in adult mutants lacking functional insulin signalling (daf-16/FOXO mutant) or TGFb signalling (daf-5/SKI and daf-7/TGFb; Supplementary Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1). A previous report has shown that DAs are produced in an insulin and TGFb signalling-dependent manner in developing C. elegans under nutrient-favourable conditions 4 . However, we found that DR also induces daf-9 expression in adult mutants lacking functional insulin signalling (daf-16/FOXO mutant) or TGFb signalling (daf-5/SKI and daf-7/TGFb; Supplementary Fig.…”
mentioning
confidence: 99%
“…Thus, our observation that DAs are produced in gravid adult worms in response to starvation contrasts with the findings in developing worms. Interestingly, DAs are also produced upon ablation of the germline, an intervention that extends lifespan in both worms and flies [4][5][6] .…”
mentioning
confidence: 99%
“…The Antebi lab (Gerisch et al, 2007) has been studying endogenous DAF-12 ligands (3-keto bile acid-like steroids), called dafachronic acids. These compounds rescue hormone-deficient mutants, such as daf-9 (cytochrome P450) and daf-36 (Rieske oxygenase), and activate DAF-12.…”
Section: Steroid Action In Specifying Longevitymentioning
confidence: 99%
“…7,[15][16][17][18][19] Additionally, three members of the nuclear hormone receptor (NHR) family of transcription regulators, DAF-12/FXR, NHR-80/HNF4 and NHR-49/PPARa are important for GSC-less longevity. 7,[20][21][22] Multiple lines of evidence have indicated that these factors link lipid metabolism to reproductive stimuli and aging. DAF-16/FOXO3A, TCER-1/ TCERG1, SKN-1/NRF2 and DAF-12/FXR targets include lipid-metabolic genes, 15,19,20,[23][24][25] PHA-4/ FOXA-and HLH-30/TFEB-mediated enhancement of autophagy contributes to increased lipase activity 17,18 and NHR-80/HNF4 promotes fatty-acid desaturation in long-lived, GSC-less adults.…”
Section: Introductionmentioning
confidence: 99%
“…7,[20][21][22] Multiple lines of evidence have indicated that these factors link lipid metabolism to reproductive stimuli and aging. DAF-16/FOXO3A, TCER-1/ TCERG1, SKN-1/NRF2 and DAF-12/FXR targets include lipid-metabolic genes, 15,19,20,[23][24][25] PHA-4/ FOXA-and HLH-30/TFEB-mediated enhancement of autophagy contributes to increased lipase activity 17,18 and NHR-80/HNF4 promotes fatty-acid desaturation in long-lived, GSC-less adults. 21 However, the generegulatory network (GRN) in which these factors operate is poorly defined and it remains unclear how their activities allow an animal to not only survive the physiological disruption created by loss of GSCs but to convert it into a beneficial enhancement of health and lifespan.…”
Section: Introductionmentioning
confidence: 99%